Evaluasi Program Buku Bergulir Model CIPP untuk Meningkatkan Literasi Membaca Masyarakat di Nagari Saok Laweh Kecamatan Kubung Kabupaten Solok - Maulina, Arinda; Ardoni, Ardoni (Lembaga Yasin AlSys, 2024)
Buku bergulir’s program implemented in Nagari Saok Laweh, Kubung District, Solok Regency is no longer as effective as it once was. One of the contributing factors is that the program was halted during the COVID-19 pandemic and only resumed in 2022. This has led to several changes, prompting a study aimed at describing the evaluation results of the buku bergulir’s program using the context, input, process, and product (CIPP) model to improve reading literacy in the community of Nagari Saok Laweh. This research is a qualitative study employing a descriptive method. Informants were selected using the snowball sampling method. Data collection was conducted through interviews and documentation. The data validation technique used in this study is triangulation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of this study indicate that (1) the context evaluation of the buku bergulir’s program is highly relevant and necessary in Nagari Saok Laweh, as the program addresses the need for quality reading materials and has great potential to improve community literacy; (2) based on the input evaluation, it was found that the program is supported by competent human resources, adequate reading materials, an efficient distribution system, and strong support from the government and the community; (3) the process evaluation of the buku bergulir’s program in Nagari Saok Laweh shows positive results, with excellent community participation and high enthusiasm; (4) through product evaluation, it was found that the buku bergulir’s program has successfully increased literacy, reading interest, and the quality of life in the community.